Attitudes of Occupational Therapists and Occupational Therapy Assistants Toward the Entry-Level Bachelor's Degree for OTAs - Randy P. McCombie (Scholarworks @ WMU, 2016)
Discussions at the local, state, and national level often focus on the value of and prospect for a change from the current entry-level master's degree to the doctorate degree as the required entrance degree for occupational therapists (OTs). While this debate is not without merit, what appears to be lacking is comparable attention to and consideration of the entry-level bachelor's degree for occupational therapy assistants (OTAs). The present study examined the attitudes and opinions of OTs and OTAs in regard to the entry-level bachelor's degree for OTAs. Responses from 144 OTs and 77 OTAs to a postal mailed survey found the majority of the participants did not agree with the profession moving to the entry-level bachelor's degree for OTAs. However, they varied significantly in responses as to whether such a move would result in OTAs being paid more or being more current in evidence-based practice/research. Further, respondents were diverse in their opinions as to whether the bachelor's degree would become the entry-level degree for OTAs in the near future. The results of this study support the need for an open national debate combined with applied research into the worth and option of moving to the entry-level bachelor degree for OTAs.